Al-doped α-MnO2 for high mass-loading pseudocapacitor with excellent cycling stability. (January 2015) - Hu, Zhimi; Xiao, Xu; Chen, Chi; Li, Tianqi; Huang, Liang; Zhang, Chuanfang; Su, Jun; Miao, Ling; Jiang, Jianjun; Zhang, Yanrong; Zhou, Jun
Abstract: The Al-doped α-MnO2 was prepared by hydrothermal method could promote the conductivity and improve the capacitance, which demonstrated by theoretical calculation and experiments. The Al doped α-MnO2 electrode with a specific capacitance of about 213 F g −1 and 146 F cm −3 under the high mass loading of 4 mg cm −2 had excellent cycling performance that of 91% maintained after 15, 000 cycles. In addition, different doping amount of Al as contrast were discussed, indicating that through modification and optimization of the chemical composition of the α-MnO2 based electrode material by Al doping could greatly improve the electrochemical behavior and to achieve higher specific capacitance. Also, we believed that the notable cycling life and high mass loading of Al doped α-MnO2 electrode material was beneficial to the application of supercapacitors. As an energy storage device, a high energy density about 2.42 mW h cm −3 with power density of 5.72 W cm −3 could be achieved. Graphical abstract: Highlights: The content of doped Al could be precisely and easily controlled through changing the feed ratio of Al 3+ to Mn 2+ . The theoretical calculation that both interstitial and substitutional Al doped α-MnO2 have been investigated. The Al-doped MnO2 microspheres exhibited the specific capacitance reaches 213 F g −1 and 146 F cm −3 with mass loading of 4 mg cm −2 . The Al-doped MnO2 microspheres shows excellent cycling stability (91% maintained after 15, 000 cycles).